CASA POPULAR COM TECNOLOGIAS SUSTENTÁVEIS - Silva, Paulo I. M. d.; Vaghetti, Marcos A. O.; Quesada, Priscila T.; Diefenbach, Samantha S.; Lana, Elinor F. D.; Souza, Alex P. d.; Antunes, Amilton S.; Fernandes, Daniel B.; GonÇAlves, Edvaldo P.; Oliveira, Jaqueline S. d.; et al. (Salão do Conhecimento, 2013)
Resumo